Preliminary Psychometric Validation of the Teammate Burnout Questionnaire - Appleby, Ralph; Davis, Paul Anthony; Davis, Louise; Stenling, Andreas; Vickery, Will (Frontiers in Psychology, 2022)
The aim of the present study was to provide support for the validation of the Teammate Burnout Questionnaire (TBQ). Athletes from a variety of team sports (N = 290) completed the TBQ and the Athlete Burnout Questionnaire (ABQ). Confirmatory factor analysis revealed acceptable fit indexes for the three-dimensional models (i.e., physical and emotional exhaustion, sport devaluation, reduced accomplishment) of the TBQ and the ABQ. Multi-trait multi-method analysis revealed that the TBQ and ABQ showed acceptable convergent and discriminant validity. The preliminary validation of the TBQ indicates the utility of the scale to reflect athletes’ perceptions of their teammates’ burnout and offers researchers the opportunity to quantitatively assess an important aspect of the social environment in the development of athlete burnout.